Soil metal/metalloid concentrations in the Clyde Basin, Scotland, UK: implications for land quality. (21st November 2018) - Fordyce, F. M.; Everett, P. A.; Bearcock, J. M.; Lister, T. R.
ABSTRACT: An assessment of topsoil (5–20cm) metal/metalloid (hereafter referred to as metal) concentrations across Glasgow and the Clyde Basin reveals that copper, molybdenum, nickel, lead, antimony and zinc show the greatest enrichment in urban versus rural topsoil (elevated 1.7–2.1 times; based on median values). This is a typical indicator suite of urban pollution also found in other cities. Similarly, arsenic, cadmium and lead are elevated 3.2–4.3 times the rural background concentrations in topsoil from the former Leadhills mining area. Moorlands show typical organic-soil geochemical signatures, with significantly lower ( P <0.05) concentrations of geogenic elements such as chromium, copper, nickel, molybdenum and zinc, but higher levels of cadmium, lead and selenium than most other land uses due to atmospheric deposition/trapping of these substances in peat. In farmland, 14% of nickel and 7% of zinc in topsoil samples exceed agricultural maximum admissible concentrations, and may be sensitive to sewage-sludge application. Conversely, 5% of copper, 17% of selenium and 96% of pH in farmland topsoil samples are below recommended agricultural production thresholds. Significant proportions of topsoil samples exceed the most precautionary (residential/allotment) human-exposure soil guidelines for chromium (18% urban; 10% rural), lead (76% urban; 45% rural) and vanadium (87% urban; 56% rural). For chromium, this reflects volcanic bedrock and the history of chromite ore processing in the region. However, very few soil types are likely to exceed new chromiumVI-based guidelines. The number of topsoil samples exceeding the guidelines for lead and vanadium highlight the need for further investigations and evidence to improve human soil-exposure risk assessments to better inform land contamination policy and regeneration.